2017
DOI: 10.1177/1010428317702901
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-induced enhancement of MCF-7 breast cancer cell response to 5-fluorouracil and cyclophosphamide

Abstract: The study was designed to evaluate the potential use of insulin for cancer-specific treatment. Insulin-induced sensitivity of MCF-7 breast cancer cells to chemotherapeutic agents 5-fluorouracil and cyclophosphamide was evaluated. To investigate and establish the possible mechanisms of this phenomenon, we assessed cell proliferation, induction of apoptosis, activation of apoptotic and autophagic pathways, expression of glucose transporters 1 and 3, formation of reactive oxygen species, and wound-healing assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…Indeed, it regulates carbohydrate and lipid metabolism, stimulates DNA synthesis, modulates transcription [118], and stimulates the cellular uptake of various nutrients, including glucose, by facilitated diffusion [119]. Agrawal et al studied the effect of insulin on the sensitivity of a breast cancer cell line (MCF-7) to 5-fluorouracil (5FU) and cyclophosphamide (CPA) [120]. The chemotherapeutic agents 5FU and CPA are widely used in the clinic and incorporated in the treatment of several cancer, including breast cancer, being associated with increased levels of chemoresistance.…”
Section: Insulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it regulates carbohydrate and lipid metabolism, stimulates DNA synthesis, modulates transcription [118], and stimulates the cellular uptake of various nutrients, including glucose, by facilitated diffusion [119]. Agrawal et al studied the effect of insulin on the sensitivity of a breast cancer cell line (MCF-7) to 5-fluorouracil (5FU) and cyclophosphamide (CPA) [120]. The chemotherapeutic agents 5FU and CPA are widely used in the clinic and incorporated in the treatment of several cancer, including breast cancer, being associated with increased levels of chemoresistance.…”
Section: Insulinmentioning
confidence: 99%
“…This effect of insulin was linked to enhancement of apoptosis, activation of apoptotic and autophagic pathways, and to overexpression of GLUT1 and GLUT3 as well as to inhibition of cell proliferation and motility (Table 2). Therefore, it was concluded that insulin sensitization before chemotherapy treatment could overcome chemoresistance [120]. The effect of insulin upon GLUT1 and GLUT3 protein expression levels were hypothesized to be mediated by the PI3K-Akt pathway, but the hypothesis was not tested.…”
Section: Insulinmentioning
confidence: 99%
“…Insulin has the ability to enhance the cytotoxic effect of chemotherapy in vitro ( 43 ), which may explain the observed decreased recurrence-risk among overweight or obese chemotherapy-treated patients with nuclear InsR + tumors in this study. The interplay between InsR, ER and IGF1R emphasizes the importance of combining the expression of nuclear InsR and ER and their impact as prognostic and treatment predictive biomarkers needs further elucidation.…”
Section: Discussionmentioning
confidence: 66%
“…Due to its complex influence on malignant cell metabolism, insulin has been exploited as a potential sensitizing agent in cancer therapy. Several in vitro and clinical studies have found that the inhibitory effect of various cytotoxic agents can be enhanced in the presence of insulin [ 21 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its impact on cellular uptake of many compounds including glucose by facilitated diffusion has been documented [ 20 ]. The use of insulin for cancer-specific treatment has been tested in several studies [ 21 25 ].…”
Section: Introductionmentioning
confidence: 99%